Pengembangan Inovasi Produk, Marketing Strategy, dan Rebranding Plan UMKM Warung Moro Wareg, Kabupaten Kediri - Ningsih, Anik Kurnia; Ningsih, Nuraini Kusuma; Pertiwi, Rizka Dwi Yulian; Suryani, Meina Putri; Arisetyawan, Kukuh (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
Small and Medium Enterprises (MSMEs) have an important role in the Indonesian economy, but face various challenges, both from internal and external factors. Marketing that is less than optimal is one of the common problems. Product image and innovation are the keys to achieving consumer satisfaction. This research aims to design product innovation, marketing strategies and rebranding to increase consumer interest in the MSME case study, Warung Moro Wareg in Kediri Regency. The research uses primary data obtained through observation, interviews with stall owners, and questionnaires distributed to consumers aged 20-54 years in Ngasem District, Kediri Regency. Analysis was carried out using the SWOT, IFAS, EFAS and Quantitative Strategic Planning Matrix (QSPM) matrices. The results of the SWOT analysis show the strengths of a variety of menus and strategic locations, while weaknesses include a lack of workers and limited operational hours. Opportunities are factory worker customers and online ordering, while threats are competition and menu imitation. IFAS and EFAS analysis identified Warung Moro Wareg's greatest strengths and opportunities. QSPM assesses the strategy of